Conceptualization of the notion of law enforcing court discretion - Глубоченко, С. М. (Theory and practice of jurisprudence, 2016)
The understanding of law enforcing court discretion in national and foreign legal science is explored in the article; the notion and substance of ideological basis of the person carrying out court law enforcement is analyzed. The Author comes to the conclusion that gnoseological, axiological, psychological and ethical parameters of ideology of the person carrying out court law enforcement are considered to be the basis of implementation of court law enforcement with the consideration to its measures